Synthesis, Characterization, and Anticancer Activities of Pyrogallol‐Based Arylspiroborates. (27th July 2015) - Cormier, Kevin; Curry, R. Daniel; Betsch, Mitchel P.; Goguen, Jeremy A.; Vogels, Christopher M.; Decken, Andreas; Turcotte, Sandra; Westcott, Stephen A.
Abstract : Arylspiroborate salts derived from pyrogallol, gallic acid, and propyl gallate have been prepared and characterized fully, including an X‐ray diffraction study for the tetrabutylammonium gallic acid complex4 . The tetrabutylammonium salts were examined for their potential anticancer activities against renal cell carcinoma (RCC) cell lines, using NBu4 [Bcat2 ] (cat = catecholato) as a control. Abstract :